Mind-body interventions for fear of cancer recurrence: A systematic review and meta-analysis - Hall, Daniel L. (Psychooncology, 2018)
OBJECTIVE: Fear of cancer recurrence (FCR) is a common existential concern and source of distress among adults with a cancer history. Multiple randomized controlled trials (RCTs) have examined mind-body approaches to mitigating FCR. We summarized characteristics of these trials and calculated their pooled effects on decreasing FCR. METHODS: Six electronic databases were systematically searched from inception to May 2017, using a strategy that included multiple terms for RCTs, cancer, mind-body medicine, and FCR. Data extraction and reporting followed Cochrane and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Pooled effect sizes on self-report measures of FCR were computed by using random-effects models. RESULTS: Nineteen RCTs (pooled N = 2806) were included. Most studies (53%) were published since 2015 and targeted a single cancer type (84%; mostly breast). Intervention sessions (median = 6, mode = 4) tended to last 120 minutes and occur across 1.5 months. Delivery was predominantly in-person (63%) to either groups (42%) or individuals (42%). Most interventions incorporated multiple mind-body components (53%), commonly cognitive-behavioral skills (58%), or meditative practices (53%). Small-to-medium pooled effect sizes were observed post-intervention (Hedges’ g = −0.36, 95% CI = −0.49, −0.23, P < .001) and at follow-up assessments (median = 8 months, P < .001). Potential modifiers (control group design, group/individual delivery, use of cognitive-behavioral or mindfulness skills, number of mind-body components, cancer treatment status, and number of sessions) did not reach statistical significance. CONCLUSIONS: Mind-body interventions are efficacious for reducing FCR, with small-to-medium effect sizes that persist after intervention delivery ends. Recommendations include testing effects among survivors of various cancers and exploring the optimal integration of mind-body practices for managing fundamental uncertainties and fears during cancer survivorship.